Current Endoscopic and Surgical Management of Pancreatic Cystic Lesions: A Comprehensive Review - Syed, Kunzah A.; Lafaro, Kelly J.; Afghan, Elham (Turkish Journal of Gastroenterology, 2024)
Pancreatic cystic lesions (PCLs) are frequent incidental findings with an increasing prevalence with age. For these significant lesions, accurate characterization of cyst type and prediction of the risk of malignant progression are crucial for specific management, such as deciding to monitor a lesion or pursue surgical intervention. Fortunately, endoscopy-based diagnostic and therapeutic techniques like endoscopic ultrasound with fine needle aspiration, confocal endomicroscopy, through-the-needle biopsy, contrast-enhanced endoscopic ultrasound, ablation, and pancreatoscopy have enabled increasingly accurate diagnoses of PCLs. Surgical management should be considered in certain cases. This narrative review’s objective is to appraise and synthesize the salient literature on the endoscopic and surgical management of PCLs to aid clinician decision-making. We analyze the current data and explore the benefits, challenges, and future prospects of endoscopy and surgery for pancreatic cysts. Cite this article as: Syed KA, Lafaro KJ, Afghani E. Current endoscopic and surgical management of pancreatic cystic lesions: A comprehensive review. Turk J Gastroenterol. 2025;36(1):6-14.